Agricultural mechanization and south-south knowledge exchange: What can Ghanaian and Nigerian policymakers learn from Bangladesh’s experience? - Aboagye, Patrick Ohene; Abubakar, Abdullahi Garba; Adama, Abdulai Iddrisu; Lawal, Akeem; Musa, Aliyu Abdullahi; Takeshima, Hiroyuki (International Food Policy Research Institute, 2016)
Past agricultural mechanization efforts in Ghana and Nigeria have focused more on the styles of machinery used in western countries or Latin America, where average farm sizes are much larger. While West African countries, particularly Ghana, are still relatively land abundant compared to Bangladesh, seeking the right balance across various models is important for achieving mechanization growth across diverse types of farms. Learning from the experience of agricultural mechanization in Bangladesh offer useful inspirations toward how widespread mechanization growth can happen for smallholders in Ghana and Nigeria.